MINYAK ATSIRI DARI Toona sinensis DAN UJI AKTIVITAS INSEKTISIDA - Adlis Santoni; Hazli Nurdin; Yunazar Manjang; Sjamsul A. Achmad (Jurnal Riset Kimia, 2009)
ABSTRACT Volatile components from leafs of Toona sinensis (Meliaceae) were isolated by distillation water-vapour method and analyzed using GC/MS. Forty-eight component were identified, and eight major components are Germacrene-D, Germacrene-B, α-Terpinene, α-Humulene, β-Caryophyllene,  α-Elemene, Bicyclogermacrene and α-copaene. Insect activity of the essential oil against Crosidolomia pavonana were tested. The activity of the essential oil with concentration 25% (mortality 73.3%), concentration 50% (mortality 83.3%) and concentration 75% (mortality 90%). Keywords : Toona sinensis (Meliaceae), essential oil, Crosidolomia pavonana, and mortality.